KESETARAAN LAYANAN KEUANGAN BAGI MASYARAKAT MISKIN SEBUAH IKHTIAR MENINGKATKAN PREFERENSI WIRAUSAHA (UMKM): PENGUATAN PERAN INTERMEDIASI SOSIAL PERBANKAN - Danial Kusumah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Regarding poverty alleviation, both nationally and globally, it has always been a priority issue for a country in its development planning. The derivative of this program, within the scope of Indonesia, is in the form of a focus on increasing the interest and capacity of MSMEs. The rational argument is that MSMEs in Indonesia are able to absorb 97% of the workforce. MSMEs are expected to be a catalyst for improving the quality of the welfare of the poor, which is supported by the synergy of the government and other stakeholders through community empowerment programs. Banks as one of the stakeholders have not made significant efforts towards poverty alleviation programs. Discrimination against economic groups is still strong in the distribution of banking financial service products. This study presents an offer of a social banking intermediation model in the form of (1) Social Entrepreneurship, (2) Distribution of social responsibility funds (CSR) to establish a business incubator, and (3) Establishment of a special institution for human resource development.